Emotional Intelligence and Prosocial Behavior in College Students: A Moderated Mediation Analysis - Wang, Haiying; Wu, Shuang; Wang, Weichen; Wei, Chao (Frontiers in psychology, 2021)
This study examined the relationship between emotional intelligence (EI) and prosocial behavior (PSB) and constructed a model for their interaction by examining the mediating effect of social support (SS) and the moderating effect of self-esteem (SE) in this relationship. A total of 742 college students aged from 18 to 20 in Northeast China ( M age =19.42 ± 0.53 years) completed a survey measuring the Emotional Intelligence Scale, Prosocial Tendencies Measurement Scale—Chinese Version, Perceived Social Support Scale, and Self-Esteem Scale. The results showed that: (1) EI positively predicted PSB; (2) SS partially mediated the relationship between EI and PSB; and (3) SE moderated the direct effect of EI on PSB and the relationship between SS and PSB. That is, when the SE of college students was higher, the effect of SS in promoting PSB was enhanced. Therefore, our results suggested that under the influence of both internal and external factors, there is an indirect effect of EI on PSB. This finding may potentially provide a theoretical basis for designing college students' mental health courses and cultivating PSB in college.